Gambaran Tindakan Pengambilan Keputusan Karir pada Siswa Kelas XII SMA Negeri 1 Sutojayan - Qanita Alifatul Azzahra; Sri Ernawati; Faqih Purnomosidi (Universitas Maritim AMNI Semarang, 2025)
Adolescence is a time when we, as students, are required to have the ability to make career decisions. Career selection is an important part of the decision-making process in the life of every individual. The purpose of this study was to determine the description of career decision-making actions in class XII students of SMA Negeri 1 Sutojayan. The research method used by the author is qualitative. The number of subjects used in this study was 5 students. This study concludes that, in general, students have quite good career decision-making actions based on five aspects of career decision-making. This shows that students have sufficient awareness and readiness to face their future careers.